Retrospective analysis of patients hospitalized for febrile neutropenia - room for improvement? - Janská, Pavla; Arientová, Simona; Burantová, Anna; Holub, Michal (Klinicka mikrobiologie a infekcni lekarstvi, 2025)
OBJECTIVE: To evaluate the quality of care provided to patients with febrile neutropenia (FN) hospitalized at the Depart-ment of Infectious Diseases, Military University Hospital Prague, as a foundation for improving the management of this condition. MATERIAL AND METHODS: A retrospective observational analysis of patients diagnosed with the ICD-10 code D70 from 1 January 2015 to 1 June 2023. All evaluated parameters were selected primarily to facilitate the assessment of care quality and compliance with recommended practices. RESULTS: Of 32 evaluated patients, 19 met the criteria for FN. A history of conditions or treatments predisposing to neutropenia was noted in 74 % of patients. Seventy-four percent were admitted following evaluation or referral from an emergency department or another specialist. Blood cultures (at least two sets) were initially obtained in 80 % of cases. Antibiotics were initially administered correctly to all patients. However, considering antibiotic combinations would have been appropriate in 40 % of cases. No patients received antibiotics within one hour of initial contact with a healthcare facility. Antifungals were therapeutically administered to 58% of patients, though 37 % of these had no clear indication. A hematologist was consulted in 75 % of cases, and a stimulating factor (filgrastim) was administered in 88 % of cases. All patients were treated in isolation. An infection source was identified in 74 % of cases. CONCLUSION: The analysis highlighted areas for improving the quality of care for patients with FN. Based on this study, an internal procedure is now being developed that will focus on coordination with emergency and other departments, emphasize obtaining blood cultures, and ensure the timely and correct administration of antibiotics, including their possible combinations, as well as antifungals.
Keywords: mužské pohlaví; Retrospective Studies; Male; senioři; retrospektivní studie; Female; Humans; lidé; antifungal agents filgrastim.; Anti-Bacterial Agents; Middle Aged; ženské pohlaví; lidé středního věku; antibiotics; febrile neutropenia; Febrile Neutropenia; blood culture; Quality of Health Care; Hospitalization; dospělí; antibakteriální látky; Adult; kvalita zdravotní péče; febrilní neutropenie; antifungální látky; Aged; Antifungal Agents; hospitalizace